Digital Competencies Among University Teachers in Ghana: Enhancing Innovative Approaches for Effective Teaching and Learning - Ibrahim, Mohammed Gunu (Advances in Social Sciences Research Journal, 2025)
This study investigated the digital competencies of university teachers in Ghana, focusing on their ability to integrate and utilize digital technologies in their teaching practices. The research assesses various aspects of digital competencies, including the teachers’ self-assessment of their skills, the digital infrastructure available in their institutions, and the degree to which digital technologies are integrated into the teaching and learning process. A questionnaire survey was conducted with 100 randomly selected university teachers, with data analysed using frequency analysis. The study found that most teachers reported a moderate to high level of competence in areas such as online course management and digital assessment techniques. The research also highlights the growing role of digital technologies in higher education, noting their potential to improve teaching effectiveness, student engagement, and research productivity. Challenges hindering effective implementation of these digital skills included inadequate digital infrastructure, insufficient training opportunities, absence of advanced research tools, digital collaboration, and the use of multimedia content creation. The research therefore recommended policy interventions, such as improving access to digital tools, providing regular continuous professional development programs and integrating digital competencies into faculty recruitment and promotion criteria to ensure that university teachers are adequately prepared for the evolving educational landscape.